New Finds of Bronze Axes from the Carpathian Foothills - Pasterkiewicz, Wojciech; Skała, Patrycja (Analecta Archaeologica Ressoviensia, 2022)
This article presents the results of archaeological and metallurgical research on two axes made of bronze, discovered in 2020 in two locations: Izdebki, Brzozów district and Gogołów, Strzyżów district. It was possible to determine the cultural context and chronological affiliation of the artefacts. The axe from Izdebki was classified as a type with elevated edges, dated to the BrB phase and associated with the Otomani-Füzesabony culture, whereas the item from Gogołów was classified as a socketed axe with ornamented sides, dated to the period corresponding to HaB1–HaB3. An analysis of the metallurgical composition of objects was carried out, examining the cores and their surfaces (corrosion layers). It was established that both axes represent so-called tin bronzes. The discovered artefacts should probably be considered loose finds.